Decentralized, Self-Sovereign, Consortium: The Future of Digital Identity in Canada - Boysen, Andre (Frontiers in Blockchain, 2021)
This article introduces how SecureKey Technologies Inc. (SecureKey) worked with various network participants and innovation partners alongside government, corporate and consumer-focused collaborators, in a consortium approach to create a mutually beneficial network of self-sovereign identity (SSI) principles with blockchain in Canada. These principles are based on giving users ownership and control over all of their digital identity attributes as an alternative approach to the current status quo of centralized digital identity, which focuses on discrete identities are made within individual online properties. Blockchain is used as the foundation for its strong security protocols to prevent information from being identified, accessed or misused and uphold SSI principles. This paper will consider the current status quo of digital identity known as centralized digital identity and comparisons to the case study’s emphasize on the alternative thinking of SSI with principles with blockchain, which prioritizes a decentralized, self-sovereign, consortium approach as opposed to discrete identities within individual online properties. Each of these principles will be explained in detail before highlighting the practical implications, lessons learned for future applications and how both the Canadian and global identity landscapes should proceed for wider acceptance of SSI with blockchain. The case study detailed – that of Verified.Me – will demonstrate how blockchain developers can actively work to help partners transition from current identity silos to instead collaborate across varied industries and create a cohesive, secure service and digital identity network that benefits users through SSI principles and the benefits of blockchain. We also offer recommendations for how both the Canadian and global identity landscapes should proceed for wider acceptance of SSI with blockchain, the benefits of doing so and anticipated barriers affecting the adoption of future decentralized identity initiatives.